Mental Health Needs Assessment During the COVID-19 Pandemic: Consensus Based on Delphi Study - Makivić, Irena; Švab, Vesna; Selak, Špela (Frontiers in Public Health, 2021)
The COVID-19 pandemic has revealed significant gaps in mental health in terms of unrecognized and unmet needs. The goal was to accurately assess the needs and identify gaps in this area during the epidemiological crisis. A Delphi study to identify the needs was conducted with a group of decision-makers, experts, and users of mental health services. A starting point of the Delphi study was prepared in two working groups, based on recognizable international recommendations and experiences of the practitioners from the field situation. This initial set of emergency measures was supplemented through the first Delphi round, and consensus about the importance was reached in the second round. A total of 41 activities were derived, the vast majority of which were rated with a score of 4 or more. Mental health activities, which should be addressed in terms of needs, can be divided into systemic measures and service measures. This study recognizes a need to reorganize services in the direction of improving local accessibility and strengthening the network of services for immediate responses to the psychological, health, and social needs of individuals, including those arising from crisis situations, such as COVID-19 pandemic. The results of this study are in line with the international recommendations and also influenced the formulation of the Action Plan of the National Mental Health Program, while some of the measures were already implemented during the publication of the research results.